STRENGTH DETERMINATION OF LOAD-BEARING STRUCTURE OF ARTICULATED FLATCAR OF ROUND PIPES - Fomin, O. V.; Lovska, A. O. (Science and Transport Progress, 2020)
Purpose. This study aims to determine the strength of the load-bearing structure of the articulated flatcar of round pipes. Methodology. A computer model of the load-bearing structure of an articulated flatcar of round pipes has been created. To study the dynamic loading of the load-bearing structure of the flatcar, mathematical modeling was performed. The calculation is made in a flat coordinates. The oscillations of twitching, pitching and bouncing are taken into account. The motion differential equations are solved in MathCad software. Findings. It was established that the accelerations that fall upon the load-bearing structure of the first section of the flatcar are 38.2 m/s², and the second – about 37.5 m/s². The obtained acceleration values are taken into account when determining the strength indicators of the flatcar load-bearing structure. The calculation is done using the finite element method in CosmosWorks software. It is taken into account that each section of the flatcar is loaded by two 20-foot containers. The results of the calculations made it possible to conclude that the maximum equivalent stresses occur in the cantilever parts of center sill and are about 200 MPa, i.e., they do not exceed the allowable ones. The maximal displacements in the structural node are fixed in the middle parts of the sections and are 3.8 mm, the maximum deformations are 2,3·10-3. Originality. A computer model has been developed to determine the strength of the load-bearing structure of articulated flatcar made of round pipes. The model allows determining the strength indicators of the flatcar load-bearing structure with longitudinal loading of the structure. Practical value. The conducted research will increase operation efficiency of combined transportations and create recommendations on modern designing of articulated flatcars.